Discovery of thalicthuberine as a novel antimitotic agent from nature that disrupts microtubule dynamics and induces apoptosis in prostate cancer cells. Issue 5 (4th March 2018) - Levrier, Claire; Rockstroh, Anja; Gabrielli, Brian; Kavallaris, Maria; Lehman, Melanie; Davis, Rohan A.; Sadowski, Martin C.; Nelson, Colleen C.
ABSTRACT: We report for the first time the mechanism of action of the natural product thalicthuberine (TH) in prostate and cervical cancer cells. TH induced a strong accumulation of LNCaP cells in mitosis, severe mitotic spindle defects, and asymmetric cell divisions, ultimately leading to mitotic catastrophe accompanied by cell death through apoptosis. However, unlike microtubule-binding drugs (vinblastine and paclitaxel), TH did not directly inhibit tubulin polymerization when tested in a cell-free system, whereas it reduced cellular microtubule polymer mass in LNCaP cells. This suggests that TH indirectly targets microtubule dynamics through inhibition of a critical regulator or tubulin-associated protein. Furthermore, TH is not a major substrate for P-glycoprotein (Pgp), which is responsible for multidrug resistance in numerous cancers, providing a rationale to further study TH in cancers with Pgp-mediated treatment resistance. The identification of TH's molecular target in future studies will be of great value to the development of TH as potential treatment of multidrug-resistant tumors.